Elicitors of plant defenses as a standalone tactic failed to provide sufficient protection to fruits against spotted-wing drosophila - Quadrel, Amanda; Urbaneja-Bernat, Pablo; Holdcraft, Robert; Rodriguez-Saona, Cesar (Frontiers in Agronomy, 2024)
Spotted-wing drosophila, Drosophila suzukii (Matsumura), is a globally important invasive pest of soft-skinned fruits including raspberries, blueberries, and strawberries.Current control measures for this pest primarily rely on calendar-based insecticide sprays; therefore, more sustainable methods are desirable. Adults of D. suzukii use cues derived from fruits and symbiotic microbes to identify optimal sites for feeding, mating, and oviposition. We hypothesized that modifying any of these cues could influence D. suzukii adult behavior, making them less likely to select suitable fruits. One approach involves applying synthetic elicitors of the salicylic acid (SA) and jasmonic acid (JA) plant defense pathways, which are associated with defenses against pathogens and herbivores, respectively, or the use of crop sterilants, employed for microbial control, to reduce D. suzukii attraction, oviposition, and larval performance in fruits. Here, the preference and performance of D. suzukii was investigated in blueberry fruits treated exogenously with four commercial elicitors of plant defensesthree that primarily activate SA-related defenses (Actigard, LifeGard, and Regalia) and one activator of JA-related defenses (Blush)and the crop sterilant OxiDate. A series of choice and no-choice experiments were conducted in laboratory, semi-field, and field settings that were performed at various time intervals to assess the residual effects of each treatment. Our results showed no consistent repellent, oviposition deterrent, or larval toxicity activity for any of the products tested. As a result, our findings do not provide sufficient support to recommend the use of these elicitors or the crop sterilant as viable standalone options for D. suzukii management.